EDUKASI MASYARAKAT UNTUK MENGATASI LIMBAH RUMAH TANGGA DENGAN MEMBUAT PUPUK CAIR DI KURAI TAJI KECAMATAN NAN SABARIS KABUPATEN PADANG PARIAMAN - Zulkarnaini, Zulkarnaini; Sufitri, Yumita; Handayani, Suci; Nugraha, Fadil Ikhsan; Ummi, Sodaya (Jurnal Hilirisasi IPTEKS, 2025)
The accumulation of garbage in the community of Korong Talogondan, Nagari Kurai Taji, Nan Sabaris Subdistrict, Padang Pariaman District can cause foul odors and various environmental problems. Concern for treatment of the generated waste needs to be increased by enhancing understanding due to the lack of knowledge and skills among residents in waste management. Therefore, the process of managing and processing organic waste needs to be done at the source, namely households. On the other hand, farmers need fertilizers for agriculture, with prices continuously rising and soil fertility declining due to improper fertilization practices. This activity aims to provide information, knowledge, and practical experience in processing organic waste into liquid fertilizer using local microorganisms (MOL). MOL was made using kitchen waste, rice washing water, granulated sugar, and brown sugar available in every household kitchen. The activity was conducted by delivering materials on the potential of household organic waste as organic fertilizer and as an effort to overcome garbage accumulation. Increasing residents' motivation was done through direct discussions and practicing simple techniques for processing organic waste in groups. The results of this outreach show the community's interest and enthusiasm in utilizing organic waste to make liquid fertilizer, which can reduce environmental pollution, has economic value, and can provide nutrients to agricultural plants, replacing synthetic fertilizers. The production of MOL from household waste needs to be increased so that every household already has an effort to reduce garbage accumulation in order to maintain environmental quality.